2010
DOI: 10.1111/j.1748-0361.2010.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Rural Residence and the Use, Type, and Quality of Depression Care

Abstract: Objective: To assess the association between rurality and depression care. Methods: Data were extracted for 10,319 individuals with self-reported depression in the Medical Expenditure Panel Survey. Pharmacotherapy was defined as an antidepressant prescription fill, and minimally adequate pharmacotherapy was defined as receipt of at least 4 antidepressant fills. Psychotherapy was defined as an outpatient counseling visit, and minimally adequate psychotherapy was defined as ≥ 8 visits. Rurality was defined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…Antidepressants were identified using the Multum therapeutic codes available in the prescribed medicines events files. Psychotherapy was identified using the MEPS outpatient visit files [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Antidepressants were identified using the Multum therapeutic codes available in the prescribed medicines events files. Psychotherapy was identified using the MEPS outpatient visit files [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Counties outside of a metropolitan statistical area (RUCC ¼ 4-9) have been categorized into ''nonmetropolitan counties.'' Similar to other peer-reviewed literature, we use ''urban'' to refer to the metropolitan counties and ''rural'' to refer to nonmetropolitan counties (28)(29)(30)(31).…”
Section: Main Independent Variable Of Interest -County Of Residencementioning
confidence: 99%
“…3 Findings from the nationally representative Medical Expenditure Panel Survey indicate that, while rural residents with depression are significantly more likely to report receiving pharmacotherapy, they are significantly less likely to report receipt of psychotherapy. 4 Distance to a provider is a significant barrier for care, especially for older adults, 5 and recent evidence suggested that distance to a VA facility is significantly related to fewer psychotherapy services for veterans. 6 Travel time and distance are also significant predictors for receiving minimally adequate care, 6,7 which places patients at greater risk for poorer depression outcomes 8 and in some cases increased mortality.…”
mentioning
confidence: 99%